PENERAPAN KONSEP GEOGRAFI PADA BUKU TEKS GEOGRAFI TERBITAN ERLANGGA DAN ULANGAN HARIAN SEMESTER GENAP KELAS XI SMA NEGERI 2 PADANG - WELY RAHMAT ROBBI; Ahyuni ahyuni (Universitas Negeri Padang, 2022)
Abstract This study aims (1) to determine the application of the concept of geography in class XI textbooks published in Terlangga (2) to determine the application of the concept of geography to the daily test (3) to determine the percentage of LOTS, MOTS, and HOTS levels in the questions contained in the textbook and daily test, (4) to find out the application of student answers based on questions containing the concept of geography on the daily test. This study uses a quantitative method with a content analysis approach in the Geography Textbook Class XI Published by Erlanggga which analyzes the content of geography concepts in the textbook along with the questions in the book and daily Deuteronomy questions and student answers. The results showed that (1) the application of the concept of geography in textbooks was in the low category of 109 (48.2%) of 226 paragraphs (2) the application of the concept of geography to questions and daily tests was included in the low category of 120 questions, only 48 questions (40%) which contains the concept of geography and based on bloom's taxonomy that dominates are C2 (14.1%) and C3 (13.3%) (3) In achieving the bloom taxonomy the questions contained in the textbook questions have not been fully achieved because the LOTS questions dominate than the MOTS, and HOTS questions with the low category of application of geography concepts and questions in textbooks. (4) the application of student answers varied from very low to high, the dominant question was C2 or LOTS (55.5%) which was in the high category, MOTS (44.5) was in the low category, and for HOT questions there was no application. the concept of geography in it. Keywords: Textbook,Geography Concepts, Blooms Taxonomy